2020
DOI: 10.1101/2020.09.01.277293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peripapillary Perfused Capillary Density in True Versus Pseudoexfoliation Syndrome: An OCTA Study

Abstract: PurposeTo compare peripapillary perfused capillary density (PCD) among eyes with true exfoliation syndrome (TEX), eyes with pseudoexfoliation syndrome (PEX), and healthy control eyes.Materials and MethodsIn this observational cross-sectional study, eyes with and without TEX or PEX were assessed by optical coherence tomography angiography (OCTA) imaging. Bilateral OCTA images (4.5 · 4.5 mm2) centered at the optic nerve head were obtained using a commercial spectral domain OCTA system. Optic nerve head perfusion… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Three cross-sectional studies compared eyes with PXS with age-matched control eyes [20,28,37]. Regarding VD in the macular area, there was consistency in that a significant decrease in superficial VD was observed in eyes with PXS compared to controls [28,37], accompanied by a significant enlargement in the FAZ area in both the superficial capillary plexus (SCP) and deep capillary plexus (DCP) in eyes with PXS compared to control eyes [28].…”
Section: Pseudoexfoliation Syndrome Vs Controlsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three cross-sectional studies compared eyes with PXS with age-matched control eyes [20,28,37]. Regarding VD in the macular area, there was consistency in that a significant decrease in superficial VD was observed in eyes with PXS compared to controls [28,37], accompanied by a significant enlargement in the FAZ area in both the superficial capillary plexus (SCP) and deep capillary plexus (DCP) in eyes with PXS compared to control eyes [28].…”
Section: Pseudoexfoliation Syndrome Vs Controlsmentioning
confidence: 99%
“…Regarding VD in the macular area, there was consistency in that a significant decrease in superficial VD was observed in eyes with PXS compared to controls [28,37], accompanied by a significant enlargement in the FAZ area in both the superficial capillary plexus (SCP) and deep capillary plexus (DCP) in eyes with PXS compared to control eyes [28]. However, the findings related to peripapillary VD seemed to be contradictory, with Tangtammaruk et al reporting a significant decrease in peripapillary perfused capillary density in eyes with PXS versus controls [20], in line with Suwan et al [23], while Gu ¨r Gu ¨ngo ¨r et al found no significant difference in peripapillary VD between the two groups [37].…”
Section: Pseudoexfoliation Syndrome Vs Controlsmentioning
confidence: 99%
See 2 more Smart Citations